2020
DOI: 10.3390/diagnostics10060364
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinase-9 and Tissue Inhibitor of Metalloproteinase-1 in Endometriosis Menstrual Blood

Abstract: Endometriosis is a gynecological disease characterized by the presence of endometrial-like tissue outside the uterine cavity. Remodeling of the extracellular matrix (ECM) is a prerequisite for tissue implantation. The presence of matrix metalloproteinase (MMP) and its inhibitor, tissue inhibitor of metalloproteinase-1 (TIMP-1), in shed endometrium cells has a significant role in ECM degradation. A case–control study was performed to find other diagnostic markers using menstrual blood. We examined a sample of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Angiogenesis has an essential role in the establishment and growth of endometriotic lesions, regardless apoptosis [42,43]. Based on previous studies, it is shown that patients with endometriosis have much more active types of MMP-9 epithelial cells and menstrual stroma than those without endometriosis [44]. Our results in consistent with the findings of the above study confirmed the increase in migration genes (MMP2 and MMP9) of E-MenSCs compared to NE-MenSCs.…”
Section: Enhanced Migratory and Angiogenicsupporting
confidence: 92%
“…Angiogenesis has an essential role in the establishment and growth of endometriotic lesions, regardless apoptosis [42,43]. Based on previous studies, it is shown that patients with endometriosis have much more active types of MMP-9 epithelial cells and menstrual stroma than those without endometriosis [44]. Our results in consistent with the findings of the above study confirmed the increase in migration genes (MMP2 and MMP9) of E-MenSCs compared to NE-MenSCs.…”
Section: Enhanced Migratory and Angiogenicsupporting
confidence: 92%
“…Similarly, Shi and coworkers observed that the activities of MMP9 decreased in response to miR-126-5p agomir in a model of aortic smooth muscle cells transition ( 14 ). MiR-126 and MMP9 have been also suggested to play a role in development of endometriosis and MMP9 in particular, seems to be a potential marker of the disease ( 15 17 ). It has been also proposed that miR-126 acts as a tumor suppressor inhibiting proliferation, migration, and invasion by suppressing MMP2 and MMP9 expression and inactivating JAK2/STAT3 signaling pathway through targeting the EMT transcription factor ZEB1 ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of MMP-9 and TIMP-1 in the menstrual blood of endometriosis patients is related to the presence of endometriosis. (18) The imbalance between MMP-9 and TIMP-1 enhance the ectopic endometrium capability to invade and breakdown extracelullar matrix component in the process of implantation and development of endometriosis lesions. (15) However, the study about the correlation between MMP-9 activity and TIMP-1 expression with the invasion potential of endometrioma during the initial development of endometriosis has not been well explained.…”
Section: Introductionmentioning
confidence: 99%